Experimental set up for the study of plasma parameters in seeded arc plasma using Langmuir Probes inside low-cost vacuum chamber - Jha, Vijay Kumar; Mishra, Lekha Nath; Narayan, Bijoyendra (BIBECHANA, 2018)
In this piece of study, the design and development of a low cost vacuum chamber with different ports are mentioned. I-V characteristic of Langmuir Probe is obtained using the primary data of the experimental set up for ‘single probe method’ in nitrogen seeded arc plasma at atmospheric pressure The floating potential was found to be 36V and the electron density to be 1.24 ´ 104 K. Variation in electron density of the arc plasma with probe potential is also studied at low pressure range from 10 Nm-2 (0.10 mbar) to 20 Nm-2. BIBECHANA 16 (2019) 1-6